Effectiveness of Multi-Prognostic Index in older patients with advanced malignancies treated with immunotherapy. Issue 3 (April 2020) - Sbrana, Andrea; Antognoli, Rachele; Pasqualetti, Giuseppe; Linsalata, Giuseppe; Okoye, Chukwuma; Calsolaro, Valeria; Paolieri, Federico; Bloise, Francesco; Ricci, Sergio; Antonuzzo, Andrea; Monzani, Fabio
Abstract: Background: Older adults with cancer are less likely to be offered treatment for cost-benefit concern. The Multi-Prognostic Index (MPI) has been validated in various clinical settings for survival estimation. We aimed to evaluate MPI as a screening tool for older adults with cancer eligible to receive immunotherapy. Patients and Methods: Older adults with advanced or metastatic cancer, admitted to the Oncology Day Hospital of the University Hospital of Pisa from January 2017 to May 2018, eligible to receive immunotherapy were prospectively enrolled. In addition to routine oncological evaluation, each patient received a comprehensive geriatric assessment with MPI calculation. Overall survival (Cox-adjusted curve) was stratified by tertiles of MPI score. Drug toxicity was assessed according to the National Cancer Institute Common Terminology Criteria for Adverse Events (Version 4.03: June 14, 2010). Results: Seventy-nine patients [26.6% women, mean age (±SD) 74.0 ± 6.1 years] were enrolled with the following diagnosis: melanoma (51.9%), non-small cell lung cancer (25.3%), renal cell cancer (12.7%), urothelial cancer (8.9%) and Merkel cell carcinoma (1.2%). Median follow-up was 7 months (range 1–35). The patients' survival rate resulted progressively longer proceeding from the first to the third MPI tertile [HR 1.76 (0.49–6.31) Vs 2nd tertile, p < 0.05; HR 5.33 (1.68–16.89) Vs 3rd tertile, p < 0.01]. Conclusions: MPI score is an effective tool for the stratification of older patients with cancer eligible for immunotherapy with checkpoint inhibitors. Further studies are required to achieve conclusive remarks on MPI usefulness in different underlying tumor types.